Pelatihan peningkatan kompetensi jabatan fungsional penilik menuju transformasi pendidikan pada satuan pendidikan nonformal di Kabupaten Sukabumi - Yunus, Dadang; Sukmana, Cucu; Kamil, Mustofa; Hatimah, Ihat; Mutamam, Mohamad Hadi Ali Mutamam5 (Abdimas Siliwangi, 2025)
The purpose of this community service is to increase the competence of observers towards the transformation of education in non-formal education units in Sukabumi Regency. The lack of optimal observers in carrying out the main tasks of quality control of the PAUD and Dikmas programs, limited time to obtain opportunities to improve competence, limitations in the types of training for observer functional positions that can reach the dimension of space and time as well as the variety of profiles and characteristics of observers are some of the problems that exist in observers. Specifically, this service aims to: 1) describe the planning of training activities for observer functional positions towards educational transformation in non-formal education units in Sukabumi Regency, West Java, 2) describe the implementation of training activities for observer functional positions towards educational transformation in non-formal education units in Sukabumi Regency, West Java, and 3) describe the evaluation of training activities for observer functional positions towards transformation education in non-formal education units in Sukabumi Regency, West Java. The results of the service show that the training activities begin with the planning stage by conducting an analysis of the identification of training activities, including the tools that must be prepared in the training activities, namely preparation, human resources, such as participants, resource persons, and other parties involved, infrastructure, guidelines for the implementation of training in planning training activities for observer functional positions towards educational transformation in non-formal education units in Sukabumi Regency, West Java. The implementation stage of training activities is the implementation of the plan that has been prepared related to the training implementation model, approaches, strategies, methods, techniques and media used in the activity, as well as the time and place of the training. The evaluation stage is a stage to find out the extent of success in activities at the planning and implementation stage of the training activities, including reflecting on activities, distributing evaluation instruments and processing the results of the evaluation. Keywords: Training, Learners, Competencies and Non-Formal Education Units